Methodology for Nexus Approach Toward Sustainable Use of Geothermal Hot Spring Resources - Endo, Aiko; Yamada, Makoto; Baba, Kenshi; Miyashita, Yuji; Sugimoto, Ryo; Ishii, Akira; Nishijima, Jun; Fujii, Masahiko; Kato, Takaaki; Hamamoto, Hideki; Kimura, Michinori; Kumazawa, Terukazu; et al. (Frontiers in Water, 2021)
This study has developed a methodology for the nexus approach by integrating interdisciplinary and transdisciplinary concepts and qualitative and quantitative mixed methods into the process of the systems thinking approach. The nexus approach was institutionalized in two projects using the location specific case study of Beppu, Japan where a set of interconnected issues in using geothermal hot spring resources have emerged due to the promotion of geothermal energy development under low-carbon policies at global and national levels. The interlinkages among geothermal hot spring resources, including heat, steam, nutrients, and drainage between land and coastal systems were analyzed to improve decision- and policy-making. This study discusses 1) how different discipline-oriented methods and data are integrated, 2) how much of the targeted water-energy-food nexus systems are understood using the nexus approach, and 3) how far does the nexus approach influence changes in the policy agenda and human behavior regarding sustainable geothermal hot spring resources use. The nexus approach facilitated the sequential integration of individual methods and data to better explain the causal linkages focusing on water-energy-food resources in the human-nature systems in Beppu. The proposed policy recommendations are based on the local government initiative for continuing to conduct citizen participatory surveys on geothermal hot spring resources. Transferring the developed methodology will help to effectively develop geothermal hot spring resources and compliment the current national renewable energy and natural resource policies and management.